Nanoscale Engineering of Optical Strong Coupling inside Metals (Advanced Optical Materials 2/2023). Issue 2 (18th January 2023) - Assadillayev, Artyom; Faniayeu, Ihar; Dmitriev, Alexandre; Raza, Søren
Abstract : In nickel, which is both a ferromagnet and a catalyst, electronic interband transitions (pictured in green) couple strongly to both propagating (in nanofilms) and localized (in nanostructures, controlled by their size) surface plasmons (pictured as red/blue charge oscillations), creating new hybrid matter states – plasmon‐interband polaritons – with potentially very intriguing properties and applications in photocatalysis and magneto‐optics. For further information, see article number 2201971 by Alexandre Dmitriev, Søren Raza, and co‐workers.